Social cohesion in Mexico: Content analysis of the official strategies for poverty reduction disclosed in the national development plans, 1989-2018 (Ágora de Heterodoxias, 2017)
This paper shows the proposals formulated in the National Development Plans (PND) published since 1989 to date, which are analyzed from the perspective of social cohesion proposed by Ottone and Sojo (2007). Strategies in health, housing and education are examined through discourse analysis, since they are considered factors that dilute social cohesion under the premise that it will be strengthened only if there is a linkage between social networks and institutions outside the community. The research shows that although citizen participation is a constant in the discourse embodied in the PND, it is not perceived coherence with the strategies regarding health, housing and education.
Keywords: Social Cohesion; Development; Poverty; Public Policies; Social Policy